2023
DOI: 10.3389/fphys.2022.1012729
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin integrates multidimensional regulation of Na+/K+-ATPase in ionocytes and promotes stress and ease response in hypoxia-induced air-breathing fish: lessons from integrative approach

Abstract: As circadian regulator, melatonin is involved in many physiological processes including ionosmotic regulation in fishes. Na+/K+-ATPase (NKA), an ubiquitous Na+/K+ transporter in ionocyte epithelia that drives electrochemical Na+ gradients and systemic osmotic integration, is a target of stress in fish. However, it is not certain how melatonin regulates NKA functions in ionocyte epithelia and how it modulates the adaptive response such as stress and ease response in fish particularly in hypoxia condition. We, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Zhdanova and co-workers ( 29 , 30 ) suggested that MEL promotes a sleep-like state in zebrafish. In support of MEL effects on stress alleviation, it has been also reported that this hormone mitigates other stress responses in fish, including those related to digestion, skin health, immune system function, and osmotic balance ( 18 , 36 , 73 , 74 ). All these data support the hypothesis of a role of melatonin as a recovery or alleviating hormone in fish under environmental stressors ( 74 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Zhdanova and co-workers ( 29 , 30 ) suggested that MEL promotes a sleep-like state in zebrafish. In support of MEL effects on stress alleviation, it has been also reported that this hormone mitigates other stress responses in fish, including those related to digestion, skin health, immune system function, and osmotic balance ( 18 , 36 , 73 , 74 ). All these data support the hypothesis of a role of melatonin as a recovery or alleviating hormone in fish under environmental stressors ( 74 ).…”
Section: Discussionmentioning
confidence: 86%
“…In support of MEL effects on stress alleviation, it has been also reported that this hormone mitigates other stress responses in fish, including those related to digestion, skin health, immune system function, and osmotic balance (18,36,73,74). All these data support the hypothesis of a role of melatonin as a recovery or alleviating hormone in fish under environmental stressors (74). In this sense, a recent study has also revealed that MEL ameliorates silver nanoparticles-induced toxicity effects in Nile tilapia, Orechromis niloticus (75).…”
Section: Discussionmentioning
confidence: 89%